Advancing genome editing to improve the sustainability and resiliency of animal agriculture - Diane Wray-Cahen; Anastasia Bodnar; Caird Rexroad; Frank Siewerdt; Dan Kovich (CABI Agriculture and Bioscience)
Abstract Animal agriculture faces unprecedented challenges, including the need to increase productivity to meet increasing demands for high quality protein while combating increasing pest and disease pressures, improving animal welfare, adapting to a changing climate, and reducing the environmental impact of animal agriculture. Genome editing, in concert with other existing technologies, has the potential to accelerate these efforts. The U.S. Department of Agriculture (USDA) supports research focused on delivering scientific solutions to these national and global agricultural challenges and transferring these solutions to farmers. Genome editing, along with a broad range of other tools, provides an opportunity for scientists, breeders, farmers, and ranchers to meet these challenges and provides additional benefits for society, including healthier and more resilient livestock, while reducing agriculture’s impact on the environment. Farmers and ranchers need a full toolbox of existing and innovative options. However, they will not be able to access these tools unless flexible approaches are in place that encourage innovation and allow safe innovations to be used on farms. Genome editing can help us achieve these goals only if global regulatory and policy approaches allow their use in agricultural breeding programs and deployment to farms. The global regulatory landscape for products of genome editing is rapidly evolving, with an increasing number of countries focusing more on characteristics of products and whether they could be achieved by conventional breeding, rather than the technologies used to create them. The livelihoods of people along the agricultural value chain depend upon countries’ regulatory and policy choices; regulatory approaches and how they are applied have a dramatic impact in determining what products are developed and who can afford to use these new biotechnologies. We need to step forward and continue the momentum towards regulatory approaches that encourage innovation to ensure continued access to a safe, abundant, and affordable food supply for future generations.